Two new species of the shieldtail snake genus Rhinophis Hemprich, 1820 (Serpentes: Uropeltidae), from the Rakwana and the Knuckles Massifs of Sri Lanka - Gower, David J.; Sampaio, Filipa L.; Vidanapathirana, Dulan Ranga; Wickramasinghe, L. J. Mendis (Zootaxa, 2024)
Two new species of the uropeltid snake genus Rhinophis Hemprich, 1820 are described from Sri Lanka. Rhinophis martin sp. nov. is described from 11 type specimens from the Rakwana Massif, and another 22 specimens from the same region are referred to this new species. Rhinophis dinarzardae sp. nov. is described from eight type specimens from the Knuckles Massif, and another 64 specimens from the Knuckles and adjacent hills are referred to this new species. Rhinophis martin sp. nov. has apparently not been reported previously under any scientific name, but is distinct in scalation, colour pattern and DNA. Rhinophis dinarzardae sp. nov. has long-been confused with the superficially similar R. philippinus, from which it differs by having more ventral scales, by occurring in the northern part of the Knuckles Massif and adjacent hills to the West rather than in the Central Highlands upland region (and possibly areas to the South and West) of Sri Lanka, and in DNA sequence data. The new descriptions take the inventory of currently recognised, named uropeltid species in Sri Lanka to 20, all members of the genus Rhinophis.